2018
DOI: 10.4103/jmas.jmas_155_17
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes of laparoscopic-assisted surgery, mini-laparotomy and conventional laparotomy in patients with Stage I-III colorectal cancer

Abstract: Background:Three operative techniques have been used for colorectal cancer (CRC) resection: Conventional laparotomy (CL) and the mini-invasive techniques (MITs)– laparoscopic-assisted surgery (LAS) and mini-laparotomy (ML). The aim of the study was to compare the short- and long-term outcomes of patients undergoing the three surgical approaches for Stage I–III CRC resection.Patients and Methods:This study enrolled 688 patients with Stage I–III CRC undergoing curative resection. The primary endpoints were perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…We further checked patients who died for their mean survival time within one year between conventional and MLS approach were 0.51 (n = 25, 11.8% of 212 matched CS group) and 0.74 years (n = 6, 2.8% of 212 matched MLS group), respectively; overall 52% of CS death and 33% of MLS death died within 180 days; 84% of CS death and 100% of MLS death due to CRC cause of death based on ICD-9-CM code 153 and 154. Several empirical evidences also suggested that mini-laparotomy seems a feasible, minimally invasive and safe alternatives to conventional laparotomy for Stage I-III CRC resection [11, 13, 36]. However, given the limitation of the current observational study using small sample size and the short-term follow-up period within one-year, caution is needed when interpreted the observed the potential benefit of MLS in reducing mortality between matched CS and MLS cohorts.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We further checked patients who died for their mean survival time within one year between conventional and MLS approach were 0.51 (n = 25, 11.8% of 212 matched CS group) and 0.74 years (n = 6, 2.8% of 212 matched MLS group), respectively; overall 52% of CS death and 33% of MLS death died within 180 days; 84% of CS death and 100% of MLS death due to CRC cause of death based on ICD-9-CM code 153 and 154. Several empirical evidences also suggested that mini-laparotomy seems a feasible, minimally invasive and safe alternatives to conventional laparotomy for Stage I-III CRC resection [11, 13, 36]. However, given the limitation of the current observational study using small sample size and the short-term follow-up period within one-year, caution is needed when interpreted the observed the potential benefit of MLS in reducing mortality between matched CS and MLS cohorts.…”
Section: Discussionmentioning
confidence: 95%
“…The MLS approach for the process innovation group was defined as curative resection performed through a skin incision less than or equal to 8 cm in length and were performed by using traditional surgical techniques and instruments. Patients were not eligible to receive MLS procedure and were excluded entirely based on the following criteria: 1) patients who did not consent to the procedure; 2) patients with tumors larger than 8 cm in size or with tumors that were infiltrating adjacent organs; 3) patients who had a previous abdominal operation; 4) patients who had either multiple carcinomas of the colon or adenomatous polyposis coli ; 5) patients with severe intra-abdominal adhesions due to a prior laparotomy, 6) patients who had larger than the value of 28 in body mass index (BMI) [11, 13, 36], and 7) patients with acute total obstruction or perforation complications were also excluded. To avoid the potential selection bias, the above criteria were also applied upfront as exclusion criteria for the open surgery comparison group in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical data of all patients were retrospectively collected by reviewing the medical records. All three groups received the same postoperative care and surveillance, as per previous study principles [13].…”
Section: Patient Population and Clinical Data Collectionmentioning
confidence: 99%
“…All three groups received the same postoperative care and surveillance, as per previous study principles [13].…”
Section: Patient Population and Clinical Data Collectionmentioning
confidence: 99%